Dietary effects of organic selenium and zinc combination on in vitro microbial dynamics in the rumen (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study used an in vitro approach to investigate the effects of combined organic selenium and zinc supplementation on rumen microbial communities. Materials and Methods: A completely randomized design was employed with five dietary treatments: basal diet only (CON), CON + selenium 0.30 ppm (part per million) + zinc 60 ppm (SZ-1), CON + selenium 0.45 ppm + zinc 60 ppm (SZ-2), CON + selenium 0.30 ppm + zinc 90 ppm (SZ-3), and CON + selenium 0.45 ppm + zinc 90 ppm (SZ-4). Selenium and zinc were provided in the form of organic-chelated methionine. Results: Analysis of rumen microbiota through 16S rRNA gene sequencing showed no significant differences in microbial diversity (p > 0.05); however, microbial composition was significantly affected. SZ-2, SZ-3, and SZ-4 groups exhibited an increased prevalence of Bacteroidetes and Proteobacteria and a reduction in Firmicutes compared to CON and SZ-1 (p < 0.05). The relative abundance of Patescibacteria and Euryarchaeota was also reduced in the SZ-2, SZ-3, and SZ-4 groups (p < 0.05). At the genus level, Prevotella, Ruminococcus, and Rikenellaceae RC9 gut groups were enriched in SZ-2, SZ-3, and SZ-4, whereas Lachnospiraceae XPB1014 and Christensenellaceae R-7 group decreased (p < 0.05). Conclusion: Combined selenium and zinc supplementation as organic trace minerals significantly modulates rumen microbial composition, enhancing the relative abundance of carbohydrate-degrading bacteria while reducing methanogen-related taxa.J. Adv. Vet. Anim. Res., 12(3): 795–805, September 2025http://doi.org/10.5455/javar.2025.l942